DIVERSIFIKASI PERUSAHAAN, STABILITAS LINGKUNGAN, KEPEMILIKAN MANAJERIAL DAN PENGARUHNYA TERHADAP KINERJA: SEBUAH AGENDA PENELITIAN - Gunarso Wiwoho (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
Various studies and opinions are still debating whether to bring the benefits of diversification or even a negative impact on long-term competitive advantage. On one side argued that the company can increase the diversification of economies of scale. While on the other hand a lot of opinions that the strategy to focus on core competencies is the key to the company's advantage in the long run. This study provides evidence of the diversification of the company and its consequences on firm value. Diversified company as part of the internal market mechanisms can have benefits and costs on the performance of the company. The purpose of this study was to find empirical evidence of (a) the effect of corporate diversification on firm performance, (b) the effect of managerial ownership on the relationship between corporate diversification and firm performance, (c) the effect of environmental stability on the relationship between corporate diversification and firm performance.